Smart Aquarium with IoT based as Monitoring in Fish Farming - Junaedi Junaedi; Hok Ki (bit-Tech, 2022)
The development of science and technology has developed rapidly at this time and will have a positive impact to facilitate human activities, including aquarium ornamental fish hobbyists. The problems encountered are, ornamental fish sellers who have difficulty monitoring all aquarium conditions and feeding and for people who are very busy and even indifferent to monitoring and feeding their ornamental fish. This tool has a water heater as well as a water temperature and pH sensor that can directly monitor the conditions in the aquarium. Arduino Uno is the mainboard that is used to control all sensors with Internet of Things (IoT) including : water temperature sensors, water turbidity sensors, water level sensors, water pH sensors, automatic lights, water heaters that will automatically turn on when the temperature is low and will automatically turn off when they reach the specified temperature and ESP8266-01 which functions to communicate between the Board and the smartphone, as well as the components of the tool and its uses are in accordance with requests from users obtained through Requirement Elicitation. Through the BlackBox trial, it includes low temperature testing of the water which makes the water heater automatically turn on and the water heater turns off when it reaches the specified temperature, monitoring water pH, water temperature, water level, water turbidity, on & off lights and feeding fish manually via a smartphone. And for the results of the Smart Aquarium trial, it can be operated with an Android smartphone, at least Android OS 4.3 and above.